Sirkulasi Linen Room Dalam Sistem Kerja Housekeeping di Hotel Four Points By Seraton Manado - Bet E.S Lagarense; Jonzon Jonzon; Jemmy R Pangemanan; Vesty L Sambeka (HOSPITALITI DAN PARIWISATA, 2022)
Analysis of the flow of linen room circulation in the housekeeping work system at the Four Points by Seraton Manado Hotel. This research is about the linen room circulation flow in the housekeeping work system.The purpose of this study is to analyze the linen room circulation flow in th housekeeping work system and to find out what problems occur in the circulation flow system.The research method used is the descriptive qualitative research ethod as it can be interpreted as a problem-solving procedure investigated by describing a subject or object in the study, which can be staff, company customers, and even society at this time.The qualitative data analysis technique is inductive, namely an analysis based on te data obtained, then a certain relationship pattern is developed or becomes a hypothesis. The results of this study indicate that the problem in the flow of linen circulation is true, namely the distribution of clean linen is often late, resulting in roomboy delays in completing the rooms.